Presentation of business conditions of Ukraine from the perspective of the trade with Poland - Ślusarczyk, Bogusław; Halicki, Marcin (НГУ, 2012)
Ukraine is the state bordered by Poland and has a large number of population, amounting approximately to 45,2 million in 2011 [12] (in Poland it amounts to about 38,3 million [12]). Thus, having a large market, the country contributes to a very attractive business from the perspective of cooperation with Poland.
Keywords: економіка України; зовнішня торгівля України; економіка Польші; научная публикация НГУ 2012